High Iron Stores in the Low Malaria Season Increase Malaria Risk in the High Transmission Season in a Prospective Cohort of Rural Zambian Children. Issue 8 (12th July 2017) - Barffour, Maxwell A; Schulze, Kerry J; Coles, Christian L; Chileshe, Justin; Kalungwana, Ng'andwe; Arguello, Margia; Siamusantu, Ward; Moss, William J; West, Keith P; Palmer, Amanda C
Abstract: Background: Higher iron stores, defined by serum ferritin (SF) concentration, may increase malaria risk. Objective: We evaluated the association between SF assessed during low malaria season and the risk of malaria during high malaria season, controlling for inflammation. Methods: Data for this prospective study were collected from children aged 4–8 y ( n = 745) participating in a biofortified maize efficacy trial in rural Zambia. All malaria cases were treated at baseline (September 2012). We used baseline SF and malaria status indicated by positive microscopy at endline (March 2013) to define exposure and outcome, respectively. Iron status was defined as deficient (corrected or uncorrected SF <12 or <15 μg/L, depending on age <5 or ≥5 y, respectively), moderate (<75 μg/L, excluding deficient), or high (≥75 μg/L). We used a modified Poisson regression to model the risk of malaria in the high transmission seasons (endline) as a function of iron status assessed in the low malaria seasons (baseline). Results: We observed an age-dependent, positive dose-response association between ferritin in the low malaria season and malaria incidence during the high malaria season in younger children. In children aged <6 y (but not older children), we observed a relative increase in malaria risk in the moderate iron status [incidence rate ratio (IRR) with SF: 1.56; 95% CI: 0.64, 3.86; IRR with inflammation-corrected SF: 1.92; 95% CI: 0.75, 4.93] and high iron status (IRR with SF: 2.66; 95% CI: 1.10, 6.43; or IRR with corrected SF: 2.93; 95% CI: 1.17, 7.33) categories compared with the deficient iron status category. The relative increase in malaria risk for children with high iron status was statistically significant only among those with a concurrently normal serum soluble transferrin receptor concentration (<8.3 mg/L; IRR: 1.97; 95% CI: 1.20, 7.37). Conclusions: Iron adequacy in 4- to 8-y-old children in rural Zambia was associated with increased malaria risk. Our findings underscore the need to integrate iron interventions with malaria control programs. This trial was registered at clinicaltrials.gov as NCT01695148.